Effect of increasing dietary metabolizable protein on nitrogen efficiency in Holstein dairy cows - Muhammad Imran; Talat Naseer Pasha; Muhammad Qamer Shahid; Imran Babar; Muhammad Naveed ul Haque (Asian-Australasian Journal of Animal Sciences, 2017)
Objective The objective of the study was to determine the effects of increasing levels of metabolizable protein (MP) on lactation performance and nitrogen (N) efficiencies in lactating dairy cows. Methods Nine multiparous cows in mid lactation [113±25 days in milk] received three treatments in a 3×3 Latin square design with a period length of 21 days. The treatments were three diets, designed to provide similar energy and increasing supply of MP (g/d) (2,371 [low], 2,561 [medium], and 2,711 [high] with corresponding crude protein levels [%]) 15.2, 18.4, and 20.9, respectively. Results Increasing MP supplies did not modify dry matter intake, however, it increased milk protein, fat, and lactose yield linearly. Similarly, fat corrected milk increased linearly (9.3%) due to an increase in both milk yield (5.2%) and milk fat content (7.8%). No effects were observed on milk protein and lactose contents across the treatments. Milk nitrogen efficiency (MNE) decreased from 0.26 to 0.20; whereas, the metabolic efficiency of MP decreased from 0.70 to 0.60 in low to high MP supplies, respectively. The concentration of blood urea nitrogen (BUN) increased linearly in response to increasing MP supplies. Conclusion Increasing MP supplies resulted in increased milk protein yield; however, a higher BUN and low MNE indicated an efficient utilization of dietary protein at low MP supplies.